2017
DOI: 10.11611/yead.316847
|View full text |Cite
|
Sign up to set email alerts
|

Sürdürülebi̇li̇rli̇k Yatirimlarinin Fi̇nansal Performansa Etki̇si̇: Türki̇ye Örneği̇

Abstract: Uluslararası literatürde sürdürülebilirlik ve finansal performans ilişkisini inceleyen çalışmalar birbirleri ile çelişen bulgular ortaya koymuşlardır. Her ne kadar sürdürülebilirlik etkisini pozitif bulan çalışma sayısı daha fazla olsa da ciddi miktarda çalışma ilişkiyi negatif bulmuş, yine birçok çalışma da herhangi anlamlı bir ilişki bulamamıştır. Bu durum ilişkinin yönü hakkında ciddi kuşku oluşturmaktadır ve dahası böyle bir ilişkinin var olup olmadığı hala önemli bir araştırma sorusu olarak gündemini koru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The studies about sustainability in the finance sector is limited in literature. And most of the studies excluded finance sector from their samples (Soytaş et al 2017;Burhan & Rahmanti, 2012;Aggarwal 2013). The reason for this is that the responsibilities of finance sector concerning pollution and labor safety are less in contrast to other sectors.…”
Section: Model Data and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The studies about sustainability in the finance sector is limited in literature. And most of the studies excluded finance sector from their samples (Soytaş et al 2017;Burhan & Rahmanti, 2012;Aggarwal 2013). The reason for this is that the responsibilities of finance sector concerning pollution and labor safety are less in contrast to other sectors.…”
Section: Model Data and Methodologymentioning
confidence: 99%
“…According to the table, when we check methods and results of publications, we see that Burhan & Rahmanti (2012), Madorran & Garcia (2016) could not find a relationship between sustainability performance and financial performance by the method panel data. , Soytaş et al (2017), Düzer & Önce (2018) and Önder (2018) found a positive relationship between sustainability performance and financial performance by the method panel data.…”
Section: Literature Reviewmentioning
confidence: 98%